These healing hills - Gabhart, Ann H., 1947- (Revell, a division of Baker Publishing Group, 2017)
"When a young woman's plans for her future fall apart at the close of World War II, she discovers new purpose as a midwife in the hills of Kentucky--and a possible chance at new love"--